Research Trend of User-Generated Content in Tourism - Batara Nobon Siregar; Ari Sulistyanto; Hamida Syari Harahap; Wichitra Yasya; Dwinarko Dwinarko (Dinasti Publisher, 2024)
The habit of sharing travel experiences on social media is increasingly attached to modern life today, making the theme of User Generated Content (UGC) in tourism never be uninteresting topic to research. Research on UGC in tourism grew 30.31% over the last 10 years. This study uses a bibliometric approach to analyze the database from Scopus with the keyword